2021
DOI: 10.1016/j.bpj.2021.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-dependent mechanism of membrane insertion and destabilization by the SARS-CoV-2 fusion peptide

Abstract: Cell penetration after recognition of the SARS-CoV-2 virus by the ACE2 receptor, and the fusion of its viral envelope membrane with cellular membranes, are the early steps of infectivity. A region of the Spike protein (S) of the virus, identified as the “fusion peptide” (FP), is liberated at its N-terminal site by a specific cleavage occurring in concert with the interaction of the receptor binding domain of the Spike. Studies have shown that penetration is enhanced by the required binding of Ca 2+… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
80
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 51 publications
15
80
0
1
Order By: Relevance
“…RBD, receptor-binding domain (red); RBM, receptor-binding motif (yellow); SD1, subdomain 1; SD2, subdomain 2; FP, fusion peptide; S1, subunit 1 (blue); S2, subunit 2 (cyan). Since this field is still under global scientific investigation, a number of published sources, including the UniProt entry P0DTC2, were used to identify each domain along with their start and end locations[50][51][52][53][54][55][56][57][58][59].…”
mentioning
confidence: 99%
“…RBD, receptor-binding domain (red); RBM, receptor-binding motif (yellow); SD1, subdomain 1; SD2, subdomain 2; FP, fusion peptide; S1, subunit 1 (blue); S2, subunit 2 (cyan). Since this field is still under global scientific investigation, a number of published sources, including the UniProt entry P0DTC2, were used to identify each domain along with their start and end locations[50][51][52][53][54][55][56][57][58][59].…”
mentioning
confidence: 99%
“…The FP2 peptide was the least effective in promoting membrane fusion and leakage in the conditions tested. However, it has been shown that the binding of Ca 2+ ions triggers FP2 membrane insertion and membrane order to the FP2 Asp and Glu residues [17] , [40] , [53] , and this binding is highly specific [42] . Therefore, it is tempting to investigate whether the low membrane fusion activity displayed by FP2H7 would be enhanced by Ca 2+ binding.…”
Section: Resultsmentioning
confidence: 99%
“…For the FP2H7-membrane fusion assays, we used LUVs comprised of 60% POPC, 20% of the anionic POPS, and 20% cholesterol (molar ratio), a lipid model membrane used in other fusion peptide studies [23] , [40] , [53] . The Ca 2+ -dependent SARS-CoV FP2H7 membrane insertion and membrane-ordering effect are virtually identical in POPS- and POPG-containing membranes [17] , [42] .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, calcium triggers protease-mediated membrane fusion activation of SARS-CoV-2 [ 46 ], while phosphorylated residues Y789 and T791 [ 47 ] near the N-terminus of FP may increase the negative charge and facilitate the accumulation of Ca 2+ ions. Besides, in the absence of Ca 2+ ions, membrane binding of FP will be reduced drastically [ 48 ], along with the fusion peptide binding two Ca 2+ ions whose binding sites show greater synergy [ 49 ]. Therefore, it can be seen that the combination of Ca 2+ ions with the FP can enhance penetration that changes the molecular organization of a specific area on the double layer to a greater extent.…”
Section: Introductionmentioning
confidence: 99%